Sexual Dimorphism of Calvarial Thickness Parameter in Different Skeletal Patterns (Mustansiria Dental Journal, 2018)
The purpose of the current study was to evaluate the calvarial thickness parameterin both genders, and in different skeletal patterns. The sample included 120pretreatment digital lateral cephalometric radiographs of Iraqi subjects (60 males and60 females) aged between 17 to 30 years, attending Orthodontic Clinic in the Collegeof Dentistry; Baghdad University, and private clinics in Baghdad city. The 120radiographs were divided into 3 groups (40 radiographs for each group) according tothe ANB angles: ANB angle smaller than one degree (Class III), between two andfour degrees (Class I), and larger than four degrees (Class II), each group was furthersubdivided into two subgroups according to gender (20 radiographs for each gender).Four linear measurements were used exclusively in the assessment of calvarialthickness parameter in both genders.The mean calvarial thickness values changed from highest to lowest in sphenoid,parietal, occipital, and frontal bones respectively. In the skeletal class II malocclusionthe frontal and occipital bones' thickness showed highly significant gender differences(P